Lingual alveolar soft part sarcoma responsive to pazopanib: A case report. Issue 44 (November 2017) - Yoshihiro, Tomoyasu; Tsuchihashi, Kenji; Nio, Kenta; Arita, Shuji; Nakano, Takafumi; Yasumatsu, Ryuji; Jiroumaru, Rina; Ariyama, Hiroshi; Kusaba, Hitoshi; Oda, Yoshinao; Akashi, Koichi; Baba, Eishi
Abstract: Rationale: The multi-targeted tyrosine kinase inhibitors such as cediranib, sunitinib and pazopanib have been reported to be effective for alveolar soft part sarcoma (ASPS). The efficacy of pazopanib for the patient with lingual ASPS has yet to be reported. Patient concerns: A 23-year old man presented with articulation disorder and swelling of the tongue. Diagnosis of lingual ASPS was made after incisional biopsy and complete excision of the mass was performed. Three months later, he presented with a protruding mental region. Diagnoses: Computed tomography revealed mental region mass and lung metastasis. Interventions: After the failure of combination therapy of doxorubicin and ifosfamide, pazopanib was administered. Outcomes: Shrinkage of both the mental region and lung mass continued for more than two months, but regrowth was confirmed at the fourth month. Lessons: Lingual ASPS is an exceedingly rare subset of ASPS with distinct molecular and histological characteristics and appropriate therapy remains to be established. Our findings suggest a possible therapeutic strategy for lingual ASPS.